Penerapan Prinsip Assessment For Learning dalam Metode Sorogan Kitab Fathul Qarib di Pesantren: Studi Multi Situs - M. Musthofa Asy’ari; Akbar Muharom; Muhammad Hazballoh (Darajat: Jurnal Pendidikan Agama Islam, 2026)
Sorogan is a learning practice unique to Pesantren but few studies have examined sorogan as an assessment technique. This study aims to describe the application of the principles of assessment for learning in the implementation of the sorogan method for the Fathul Qarib textbook and to analyze the similarities and differences in its implementation. A qualitative research approach with a multi-site research design at the Pesantren Mahir Arriyadl Ringingagung and the Pesantren Fathul Ulum Kwagean. Data were collected through observation, interviews, and documentation of the sorogan implementation. The results indicate that the principles of assessment for learning are present in the implementation of the sorogan method for the Fathul Qarib text, such as clarifying learning objectives, questions and discussions, feedback, as well as peer assessment and self-assessment. The sorogan method at both Pesantren shares similarities in the muraja’ah activities and immediate feedback. The differences are evident in the approach used, namely an individual approach at the Pesantren Mahir Arriyadl and a collaborative approach at the Pesantren Fathul ‘Ulum. These differences have implications for the patterns of interaction between teachers and students, the pace of learning, and the forms of reinforcement of students’ understanding.